2021
DOI: 10.3390/s21206941
|View full text |Cite
|
Sign up to set email alerts
|

A Crack Size Quantification Method Using High-Resolution Lamb Waves

Abstract: Traditional tone burst excitation cannot attain a high output resolution, due to the time duration. The received signal is much longer than that of excitation during the propagation, which can increase the difficulty of signal processing, and reduce the resolution. Therefore, it is of significant interest to develop a general methodology for crack quantification through the optimal design of the excitation waveform and signal-processing methods. This paper presents a new crack size quantification method based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The PZT sensors are placed on each side of the crack, and all wave propagation paths in this study are perpendicular to the crack propagation, as shown in Figure 2. According to the existing research, 26 the damage indexes can be extracted from the forward-transmission Lamb waves, which contain damage information after interacting with the crack. Seven damage indexes with clear physical signification are conducted for crack damage detection under different temperatures.…”
Section: Methodology Developmentmentioning
confidence: 99%
“…The PZT sensors are placed on each side of the crack, and all wave propagation paths in this study are perpendicular to the crack propagation, as shown in Figure 2. According to the existing research, 26 the damage indexes can be extracted from the forward-transmission Lamb waves, which contain damage information after interacting with the crack. Seven damage indexes with clear physical signification are conducted for crack damage detection under different temperatures.…”
Section: Methodology Developmentmentioning
confidence: 99%
“…To enhance the detection of subtle defect signals, Zhang et al [12] harnessed time reversal theory, effectively addressing the practical limitations associated with damage scattering signals and achieving precise localization of damage in metal plates; Zhang et al [13] proposed a composite damage identification method that combines phased array ultrasonic detection with deep learning techniques, significantly improving the signal-to-noise ratio in composite ultrasonic detection. Additionally, Li et al [14] quantified crack size using highresolution Lamb wave-based approaches. Nonetheless, it is important to acknowledge that these techniques are not only operationally intricate but are also susceptible to the presence of spurious waves during the focusing process, potentially impacting the accuracy of damage detection results.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Guided wavebased SHM techniques have gained enormous interest for health management of thin plate-and shell-type structures due to their ability to detect small-sized damages and swiftly examine large regions with a limited number of transducers. [3][4][5][6][7][8][9][10][11][12] Lamb waves are generated in thin-walled structures by actuating the adhesivebonded piezoelectric transducers with electrical voltage. The propagating Lamb wave interacts with the structure and can be recorded at the same transducer (pulse-echo configuration) or a different transducer (pitch-catch configuration).…”
Section: Introductionmentioning
confidence: 99%